Do we still need a diverticuloscope for the flexible endoscopic septotomy of Zenker's diverticulum?. Issue 4 (9th December 2019) - Bresteau, Clément; Barret, Maximilien; Guillaumot, Marie‐Anne; Abou Ali, Einas; Belle, Arthur; Leblanc, Sarah; Oudjit, Ammar; Dohan, Anthony; Coriat, Romain; Chaussade, Stanislas
Abstract: Background and Aim: Zenker's diverticulum (ZD) is the most common type of diverticulum in the esophagus. The endoscopic septotomy of the diverticular wall has become a widely accepted treatment modality, but the recurrence rate is unclear. Our aim was to assess short‐term and long‐term success rates after flexible endoscopic septotomy for the treatment of ZD. Methods: All consecutive patients treated at our department for a ZD between November 2014 and September 2018 were included. Endoscopic septotomy was conducted using a diverticuloscope or a distal attachment cap. Data were retrospectively analyzed from a prospectively collected database. We collected data concerning patients, endoscopic procedures, and short‐term clinical outcomes. All patients were reached by phone between October and December 2018 to assess long‐term results. Results: Seventy‐seven patients were referred to our department for a ZD. Sixty patients were treated using a diverticuloscope and 17 patients with a distal attachment cap. For all 77 patients, the myotomy was technically successful. Three patients treated with a diverticuloscope reported complications. Initial treatment success was 93%. After a mean (±SEM) follow up of 23 ± 2 months, 66% of patients had persistent clinical remission. The rate of long‐term treatment success was 72% in treatment‐naïve and 50% in previously treated patients ( P = 0.13). Treatment success was 68% in patients treated with the diverticuloscope versus 60% in the group treated with a cap ( P = 0.75). Conclusion: The flexible endoscopic septotomy for the treatment of ZD is a safe and effective treatment of ZD, with or without a diverticuloscope.